Sposoby pomiaru i oceny efektów szkolenia pracowników - Jasiński, Zdzisław; Janiak-Rejno, Iwona (Ways of Measurement and Opinion of Effects Training Workers, 2005)
Actually people and their competences are the key factor which determinates competitiveness of organization. The most important determinate in the indicated problem is employee training. Especially in the current economic situation the firms are still looking for some proofs, so that they could justify the spending of money. In this paper was performed the some methods evaluating training effectiveness. Next based on the conducted research it was showed the real training activities and ways of training evaluating in the polish practice.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1061, s. 129-142